Assessment of a Planned Municipal Solid Waste Management System in Sri Lanka - Disna Eheliyagoda; Nimal Prematilake (Journal of Applied Sciences and Environmental Management)
Systematic Municipal Solid Waste Management (MSWM) authorities of Sri Lanka contributes to exchange  some productive outputs with localities; however it is still not in a successful mode due to limitations and environmental failures in their operation. Most of these local administrations are directly dumping Municipal Solid Waste (MSW) to an open dumping site, this manner of inappropriate disposal of MSW is become a major threat to the environment and public health in developing countries like Sri Lanka. This study was conducted for the MSWM practices of Balangoda Urban Council. The research was performed based on analyzing information obtained from field observations; reports; literature; questionnaire distribution among community; and a series of formal interviews with major stakeholders. The ongoing MSWM practices of Balangoda Urban Council encompass six categories as waste minimization and handling; waste collection; on-site separation; waste transportation; further management including grading, composting, recycling, producing sludge fertilizer; and final disposal to an open dump site. Apart from those, training sessions on MSWM are also being conducted. The purpose of this paper is to assess current status of urban waste management scenario and highlight strengths and weaknesses to understand the sustainability of the system which would help any local authority to improve MSWM. © JASEM